2004
DOI: 10.1007/s00132-003-0541-z
|View full text |Cite
|
Sign up to set email alerts
|

Das Wachstumsfaktorkomposit aus GDF-5 und mineralisiertem Kollagen verbessert die Ausheilung einer H�ftkopfnekrose

Abstract: The application of an absorbable GDF-5 composite in combination with a core decompression procedure may enhance the healing of devitalized bone defects and is a promising approach for further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…The first experimental studies have shown that GDF-5 is involved in the growth of all skeletal tissues. Thus GDF-5 has improved ligament healing (Aspenberg and Forslung, 1999;Tashiro et al, 2006), cartilage growth (Simank et al, 2004a) and (Spiro et al, 2001;Jahng et al, 2004;Simank et al, 2004b). The effect of recombinant human growth differentiation factor 5 (rhGDF-5) on membranous bone formation has been demonstrated recently by in vivo studies (Yoshimoto et al, 2006;Poehling et al, 2006).…”
Section: Discussionmentioning
confidence: 94%
“…The first experimental studies have shown that GDF-5 is involved in the growth of all skeletal tissues. Thus GDF-5 has improved ligament healing (Aspenberg and Forslung, 1999;Tashiro et al, 2006), cartilage growth (Simank et al, 2004a) and (Spiro et al, 2001;Jahng et al, 2004;Simank et al, 2004b). The effect of recombinant human growth differentiation factor 5 (rhGDF-5) on membranous bone formation has been demonstrated recently by in vivo studies (Yoshimoto et al, 2006;Poehling et al, 2006).…”
Section: Discussionmentioning
confidence: 94%
“…In addition, HA particles coated with 5 µg GDF-5 were more effective than those coated with 10 µg BMP-2 [ 49 ]). Although local release of the two BMPs in any of these different bone sites may be different, GDF-5 or its mutant BB-1 may thus still represent a valid option for bone replacement surgery [ 17 , 24 , 26 , 67 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…When the same animal model was used, BMP-14-loaded, hydroxyapatite-coated collagen scaffolds (Healos; DePuy, Warsaw, IN, USA) significantly improved bony remodeling of the necrotic area. In comparison, when the scaffold was applied without BMP-14, only partial defect filling with mainly fibrous tissue and persistence of the necrosis was seen after 12 weeks [34]. …”
Section: Growth Factor-based Strategiesmentioning
confidence: 99%